The influence of regional stress and structural control on the shape of maar craters - Nichols, Cody; Graettinger, Alison (Volcanica, 2021)
Maars are volcanic craters excavated by the interaction of magma and groundwater in subsurface phreatomagmatic explosions. Maar craters display a variety of shapes and sizes, but commonly display elongation. This paper explores the relationship between the orientation of maar elongation and regional stress indicators. The orientations of maar elongation, regional faults, and nearest neighbor lineaments containing maars were measured in seven volcanic fields: Auckland, Lamongan, Newer Volcanics Province, Pali Aike, Pinacate, San Pablo City, and Serdán Orientale. Common maar orientations were observed in several fields, and compared with faulting and nearest neighbor lineaments. It was found that the distribution of maars was commonly correlated with regional stress indicators (in lineaments), but the orientation of elongation of those maars did not always correlate with stress indicators. Maars not aligned with stress indicators were likely influenced by more local effects, including changes to the subsurface stress regime from the ongoing eruption.